Penyuluhan Pembuatan CV (Curriculum Vitae) dan Pengaplikasian LinkedIn dan Jobstreet terhadap Siswa SMKN 41 Jakarta - Aulia Zahrannissa Yunash; Hanisyah Claudya Hermanto; Kaila Aura Mevalia; Lutfi Hardiyanto (Pusat Riset dan Inovasi Nasional, 2024)
Science and Technology is one of the sciences that learns about how technology develops. This science also learns about the internet that can connect one device to another. By using the internet, we can access websites to make work easier or even find a job that we are interested in. Two examples of websites that we can visit are LinkedIn and Jobstreet. LinkedIn is one of the websites where we can do self branding and add relationships with other audiences. Meanwhile, Jobstreet is one of the websites that provides such types of jobs that we can later apply to a certain place or company. These two websites are very useful for many people, especially for vocational students who after graduating will continue their journey directly in the world of work. In this counseling, we will also teach students how to make a good and correct CV and what things distinguish between an ATS CV and a creative CV. In addition, this counsling is expected to be able to add skills and insights to students related to LinkedIn and Jobstreet so that they are more familiar with using these two platforms in their daily lives. The output results that we get through the implementation of this activity are made in the form of article and poster.